Multi-omics association study integrating GWAS and pQTL data revealed MIP-1α as a potential drug target for erectile dysfunction - Liu, Jingwen; Pan, Renbing (Frontiers in Pharmacology, 2024)
Background Erectile dysfunction (ED) brings heavy burden to patients and society. Despite the availability of established therapies, existing medications have restricted efficacy. Therefore, we utilized a two-sample Mendelian randomization (MR) approach to find the drug targets that might enhance the clinical outcome of ED. Methods Genetic instruments associated with circulating inflammatory proteins were obtained from a genome-wide association study (GWAS) involving 8,293 European participants. Summary statistics for ED were extracted from a meta-analysis of the UK Biobank cohort compromised of 6,175 cases and 217,630 controls with European descent. We utilized multi-omics method and MR study to explore potential drug targets by integrating GWAS and protein quantity trait loci (pQTL) data. Inverse-variance weighted (IVW) method was applied as the primary approach. Cochran’s Q statistics was employed to investigate the presence of heterogeneity. Furthermore, we identify the potential therapeutic drug targets for the treatment of ED utilizing molecular docking technology. Results This MR analysis of integrating GWAS and pQTL data showed that macrophage inflammatory protein-1 alpha (MIP-1α) was causally associated with the risk of ED (OR:1.19, 95%CI:1.02-1.39, P=0.023). Meanwhile, the results of the weighted median model were consistent with the IVW estimates (OR:1.26, 95%CI:1.04-1.52, P=0.018). Sensitivity analysis revealed no horizontal pleiotropy and heterogeneity. Furthermore, four anti-inflammatory or tonifying small molecular compounds, encompassing echinacea, pinoresinol diglucoside, hypericin, and icariin were identified through molecular docking technology. Conclusions This study identified MIP-1α as an underlying druggable gene and promising novel therapeutic target for ED, necessitating further investigation to detect the potential mechanisms by which MIP-1α might impact the development of ED.